An Efficient Framework for Fire Detection using Morphological Features - Tambat, Mangesh S; Kodre, Namrata; Shelke, Shubhangi; Chavan, Kimaya; Deokate, Laxman (International Journal of Computer Sciences and Engineering, 2025)
This paper gives the one of the best solution for the video surveillance in the fire detection. In the market there are most popular two software tools are used to detect the fire and smoke that are “VPlayer” for the fire and smoke detection and another one is “Precise Vision Fire Detection Graphics System” is these system one of the major drawback comes that is, user can get some times false positive result. And in this proposed system we try to reduce the false positive result. And in this system the technique involves fire features, fuzzy logic. And this proposed system is totally software based not any embedded system is used here.